A Comprehensive Force Majeure Model Clause in Corporate Transactions in Indonesia - I Gusti Agung Ayu Gita Pritayanti Dinar; I Nyoman Putu Budiartha (Fakultas Hukum, Universitas Warmadewa, 2020)
Force majeure clause is presented in various models, from the simple to the complex ones that contain comprehensive descriptions, provisions, and notifications set out in an agreement with the details of the consequences of force majeure events. Force majeure clause serves as a complementary core clause and a renegotiating tool for the parties in the case of any event occurring beyond their reasonable control, which is important enough not to be overlooked by business actors. The Covid-19 pandemic which is currently ongoing worldwide, which has been declared as a global pandemic by World Health Organization (WHO) on 11 March 2020, has had a huge impact on the social life and the world economy which is very unsettling for business people, banks, and the society in general. The research questions investigated in this study are: (i) What are the factors causing failures in the performance of contractual obligations? (ii) What is a comprehensive force majeure model clause for corporate transactions in Indonesia? This study employs the normative legal research method. A normative legal research is guided by the characteristics of the object of the research, yet remains limited by the expected outcome of the norms initially established. The theories applied in investigating the problems in this research are the will theory (wilstheorie), trust theory (vertrouwensttheorie), and statement theory (verklaringstheori). In this study, will be identified a comprehensive force majeure clause enables the party who experiences a force majeure event to waive some provisions in the contract agreement.